Optimizing Website, E-Ticketing, and Video Marketing for the Digitalization of Tirta Arum Swimming Pool’s Marketing Strategy - Muhardono, Ari; Sunarjo, Wenti Ayu; Murty, Daru Anggara; Fadhilah, Wafa Khansa; Sari, Tarismha Winda; Istianah, Laili; Syafa, Muhammad Arju; Ni'mah, Syarifatun (Society : Jurnal Pengabdian Masyarakat, 2025)
This community service activity was motivated by the low utilization of digital systems in the marketing and service strategies of Tirta Arum Swimming Pool, a business unit managed by the Village-Owned Enterprise (BUMDes) in Pekalongan Regency. Despite having an official website and e-ticketing system, observational data revealed that ticket bookings were still conducted entirely offline. This limited utilization was attributed to inadequate socialization, lack of digital promotional content strategies, and suboptimal use of social media and video marketing in reaching potential visitors. Therefore, this program was designed as a training activity focused on three main aspects: optimization of the website and e-ticketing system, development of social media-based digital marketing content strategies, and implementation of video marketing. The activity employed methods including material presentation, interactive discussions, and hands-on practice sessions with BUMDes Tirta Arum managers. Evaluation results indicated a significant improvement in participants’ knowledge and skills, as demonstrated by a comparison of pretest and posttest scores across various assessed aspects, with an average increase of over 45%. This initiative made a tangible contribution to enhancing the digital capacity of rural tourism managers and serves as a model for strengthening collaboration between universities and communities in supporting local tourism’s digital transformation.